Strength and Conditioning for Young Athletes : Science and Application - Lloyd, Rhodri S.; Oliver, Jon L. (Routledge, 2020)
Strength and Conditioning for Young Athletes: Science and Application offers an evidence-based introduction to the theory and practice of strength and conditioning for young athletes. Fully revised and updated, this second edition draws on leading research to offer a holistic approach to training centred on the concept of long-term athletic development and the welfare of the young athlete